Inhibitory effects of astilbin, neoastilbin and isoastilbin on human cytochrome CYP3A4 and 2D6 activities. (13th December 2020) - Shi, Yurui; Xie, Jing; Chen, Rongda; Liu, Guiming; Tao, Yanzhou; Fan, Yangyang; Wang, Xiaolin; Li, Li; Xu, Jiaming
Abstract: Astilbin, neoastilbin and isoastilbin are three flavonoid isomers from Smilacis glabrae Roxb. ( S. glabrae ). Several studies have shown that consumption of flavonoids can increase the risk of food/drug–drug interaction by affecting the activities of human cytochrome CYP3A4 and 2D6. In the present study, an ultrahigh‐performance liquid chromatography and triple quadrupole mass spectrometry method was developed for the determination of the interaction between three flavonoid isomers and two CYPs. Under the optimized reaction conditions, the K m values were 18.9 and 36.4 μM and the V max values were 0.02 and 0.20 μM/ min for CYP3A4 and 2D6 in vitro, respectively. Astilbin showed the strongest inhibition on CYP3A4, followed by isoastilbin and neoastilbin with IC50 values of 2.63, 3.03 and 6.51 μM . Neoastilbin showed the strongest inhibition on CYP2D6, followed by isoastilbin and astilbin, with IC50 values of 1.48, 11.87 and 14.16 μM, respectively. The three isomers showed reversible inhibition on both enzymes. Neoastilbin and astilbin were noncompetitive type for CYP3A4 and 2D6, isoastilbin was a mixture and noncompetitive type for CYP3A4 and 2D6, respectively. Our study suggests that the three isomers may increase the risk of food/drug–drug interactions by affecting the activities of CYP3A4 and 2D6.